Dividend Policy Determinants: Evidence from Emerging Economies - Jafarova, Aynur (2015)
Dividend pay-out policy has been a subject for an ongoing debate for the last few decades. Lots of researchers try to explain it through different theories while others claim its irrelevance. At the same time a number of empirical studies have been conducted based either on international or developed countries sample to find out determinants of dividend policy. This paper analyses determinants of dividend pay-out policy in emerging economies and compares them to the findings in developed countries. In the course of the research different models developed to explain dividend policies throughout the world were tested on the example of emerging market companies for 10-year period between 2003 and 2012.